Enhancing secondary school students’ science process skills through guided inquiry-based laboratory activities in biology - Ashebir Mekonnen Chengere; Beyene Dobo Bono; Samuel Assefa Zinabu; Kedir Woliy Jilo (PLoS ONE, 2025)
Science process skills (SPS) are vital for enhancing student engagement, critical thinking, and academic achievement in science education. However, Ethiopian secondary schools often rely on traditional, rote-based laboratory methods that hinder SPS development. This study examined the effect of Guided Inquiry-Based Laboratory Experiments enriched Instructional (GIBLEI) approach on improving students’ SPS in biology. GIBLEI promotes active, inquiry-based learning, encouraging students to investigate, hypothesize, experiment, and draw conclusions. By shifting from passive observation to hands-on exploration, GIBLEI addresses limitations of traditional methods, fostering deeper understanding, problem-solving skills, and reducing educational disparities in science classrooms. In this quasi-experimental study, two biology classes from selected schools were randomly assigned to experimental (EG, N = 46) and control groups (CG, N = 29). The EG received GIBLEI-based instruction for eight weeks, focusing on inquiry-based laboratory activities that require students to investigate, hypothesize, and draw conclusions. The CG, meanwhile, received traditional lab instruction with a focus on observation and confirmation of set procedures. Data on SPS development were gathered using essay tests scored with rubrics. Welch’s t-test revealed that post-test SPS scores in the EG were significantly higher than those in the CG, with a large effect size (82%), demonstrating GIBLEI’s effectiveness. ANCOVA further confirmed that the improvement was attributable to the GIBLEI approach rather than initial group differences. The Wilcoxon signed-rank test showed significant SPS improvement within the EG from pre-test to post-test, underscoring the approach’s effectiveness over time. Additionally, an independent samples t-test indicated no significant gender differences in SPS within the EG, suggesting that GIBLEI benefits both male and female students equally. The findings highlight GIBLEI as a promising tool to foster SPS, supporting its integration into biology curricula to enhance student engagement, skill acquisition, and equal learning outcomes across genders.